2006
DOI: 10.1080/00365540500333764
|View full text |Cite
|
Sign up to set email alerts
|

Ascites and highly elevated CA-125 levels in a case of peritoneal tuberculosis

Abstract: Peritoneal tuberculosis (PT) is uncommon in industrialized countries. We report the case of a 35-y-old female with a 1-y history of abdominal discomfort, ascites, systemic symptoms, and highly elevated CA-125 suggesting malignancy, in whom the diagnosis of PT was considered. Both clinical symptoms and CA-125 levels regressed under tuberculostatic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In this patient from India, who had appendiceal tuberculosis several years age, a chronic inflammation of the right adnexe developed, which had clinical and radiological features similar to ovarian cancer. Adnexitis is one of the most common intraabdominal manifestations of tuberculosis [2,13]. Our series includes no patient with HIV infection, no homeless individual and no elderly individual with reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this patient from India, who had appendiceal tuberculosis several years age, a chronic inflammation of the right adnexe developed, which had clinical and radiological features similar to ovarian cancer. Adnexitis is one of the most common intraabdominal manifestations of tuberculosis [2,13]. Our series includes no patient with HIV infection, no homeless individual and no elderly individual with reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…As the disease per se is rare in industrialized countries, very few cases of abdominal tuberculosis are described and therefore, timely diagnosis is a challenge [5][6][7]. Intraabdominal masses or peritoneal nodules together with ascites are common findings in abdominal tuberculosis but may also be suggestive for several other pathologies such as gastrointestinal or gynaecological malignancies, lymphomas, or inflammatory bowel disease [6,[8][9][10][11][12][13]. In fact several publications from industrialized countries emphasize that initial diagnosis included those mentioned above before abdominal tuberculosis was diagnosed upon laparoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, serum CA-125 is considered a nonspecific marker of peritoneal involvement. It has been reported that serum CA-125 levels are increased in patients with tuberculous peritonitis (11,12). Of note, CA-125 is expressed in the coelomic epithelium, such as the pleura, peritoneum, and pericardium (13).…”
Section: Discussionmentioning
confidence: 99%
“…19 In the present study 46 patients out of a total of 50 had elevated serum CA-125 levels at 0 months thus affirming to the observations in other studies. [20][21][22][23][24] Several studies have also observed a close correlation between the normalization of CA-125 levels with the response to anti-tuberculous therapy. 25,26 Author on present study also found a steady decline in the elevated CA-125 levels coupled with clinical improvement after initiation of antitubercular therapy.…”
Section: Discussionmentioning
confidence: 99%